Preliminary Study on the Single Nucleotide Polymorphism (SNP) of XRCC1 Gene Identificationto Improve the Outcomes of Radiotherapy for Cervical Cancer - Devita Tetriana; Wiwin Mailana; Iin Kurnia; Mukh Syaifudin (Biosaintifika: Journal of Biology & Biology Education, 2015)
Cervical cancer is the most fatal disease among Indonesian women. In recognition of the substantial variation in the intrinsic response of individuals to radiation, an effort had been done to identify the genetic markers, primarily Single Nucleotide polymorphisms (SNPs), which are associated with responsiveness of cancer cells to radiation therapy. One of these SNPs is X-ray repair cross-complementing protein 1 (XRCC1) that is one of the most important genes in deoxyribonucleic acid (DNA) repair pathways. Meta-analysis in the determination of the association of XRCC1 polymorphisms with cervical cancer revealed the potential role of XRCC1 polymorphisms in predicting cell response to radiotherapy.Our preliminary study with real-time polymerase chain reaction (RT-PCR) showed that radiotherapy affected the XRCC1 gene analyzed in blood of cervical cancer patient. Other published study found three SNPs of XRCC1 (Arg194Trp, Arg280His, and Arg399Gln) that cause amino acid substitutions. Arg194Trp is only SNPs that associated with high risk of cervical cancer but not others. Additionally, structure and function of this protein can be altered by functional SNPs, which may lead to the susceptibility of individuals to cancers. Anotherstudy found G399A polymorphisms. We concluded that SNP of this DNA repair genes have been found to be good predictors of efficacy of radiotherapy.Kanker serviks adalah penyakit yang paling fatal pada perempuan di Indonesia. Untuk memahami variasi substansial respon intrinsik individual terhadap radiasi, suatu usaha telah dilakukan untuk mengidentifikasi petanda genetik, terutama Single Nucleotide polymorphism (SNP), yang berkaitan dengan responsel kanker terhadap terapi radiasi. Satu dari SNP tersebut adalah X-ray repair cross-complementing protein 1 (XRCC1) yang merupakan satu dari gen paling penting dalam lajur perbaikan asam deoksiribonukleat (DNA). Meta-analysis dalam penentuan hubungan polimorfisme XRCC1 dengan kanker serviks menemukan adanya peranan potensial polimorfisme XRCC1 dalam memprediksi respon sel terhadap radioterapi. Studi awal kami menggunakan real-time polymerase chain reaction (RT-PCR) menunjukkan bahwa radioterapi mempengaruhi gen XRCC1yang dianalisis dalam darah pasien kanker serviks. Studi yang telah dipublikasi menemukan tiga SNP dari XRCC1 (Arg194Trp, Arg280His, dan Arg399Gln) yang menyebabkan substitusi asam amino. Arg194Trp merupakan satu-satunya SNP yang berkaitan dengan tingginya risiko kanker serviks, tetapi tidak pada yang lain. Di samping itu, strukturdan fungsi protein ini dapat berubah oleh SNP fungsional, yang mengarah ke kerentanan individu untuk menderita kanker. Studi lain menemukan polimorfisme G399A. Kami menyimpulkan bahwa SNP dari gen perbaikan DNA ini merupakan prediktor yang baik dari keberhasilan radioterapi.